Coverage for the cost of outpatient nursing procedures by the Unified Health System: a percentage analysis - Sportello, Elisabete Finzch; Castilho, Valéria; Lima, Antônio Fernandes Costa (Revista da Escola de Enfermagem da USP, 2021)
Objective: To analyze the percentage of the coverage of transfers from the Brazilian Unified Health System regarding nursing procedures conducted in the Outpatient facility of a University Hospital. Method: Quantitative, exploratory, descriptive case study. The sample for calculating the mean total direct costs was composed of non-participant observations of 656 procedures. The obtained costs were compared to transfers from the Unified Health System by multiplying the amount of procedures agreed upon by the unit cost in the Unified Table of Procedures in 2016 and 2017. Results: The Unified Health System transferred a percentage corresponding to 11.13% of the actual cost in 2016 and to 16.02% in 2017. In these two years, transfer values covered only a mean of 13.4%, resulting in a percentage difference in revenue significantly smaller than the actual cost. Conclusion: The higher the productivity of the performed procedures, the higher was the hospital deficit and, consequently, the higher were the costs not covered by the Unified Health System.